2016
DOI: 10.5817/cp2016-4-6
|View full text |Cite
|
Sign up to set email alerts
|

Help-giving and moral courage on the Internet

Abstract: The study addressed individual differences on two types of prosocial behavior on the Internet: help-giving/sharing and moral courage. A questionnaire to measure these behaviors was developed. We investigated the effects of the Big Five personality traits, sadistic traits, and values on help-giving and moral courage. We found that the willingness to help on the Internet was promoted by open personality, and the relationship was partly moderated by high weekly use of social media. The willingness to act morally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…In other words, the more adolescents use SoMe, the more OPB they display. Studies not included in this review due to time of publication (Lister, 2007 ) or focusing on another age group (Wright and Li, 2011 ; young adults, Kinnunen et al, 2016 ; adults) also support the association between SoMe use and OPB. More specifically, Lister ( 2007 ) found an association between computer-mediated communication, defined as instant messaging and visiting SoMe sites (coined as “blogging”), and OPBs among American adolescents in 7th grade (12–13 years), 9th grade (14–15 years), and 11th grade (16–17 years).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In other words, the more adolescents use SoMe, the more OPB they display. Studies not included in this review due to time of publication (Lister, 2007 ) or focusing on another age group (Wright and Li, 2011 ; young adults, Kinnunen et al, 2016 ; adults) also support the association between SoMe use and OPB. More specifically, Lister ( 2007 ) found an association between computer-mediated communication, defined as instant messaging and visiting SoMe sites (coined as “blogging”), and OPBs among American adolescents in 7th grade (12–13 years), 9th grade (14–15 years), and 11th grade (16–17 years).…”
Section: Discussionmentioning
confidence: 89%
“…Wright and Li ( 2011 ) found that time spent using electronic technologies was correlated with OPB through that particular technology, such as social networking sites, chat programs, email, and text-messages, among young adults (mean age = 20 years). Kinnunen et al ( 2016 ) found that the use of SoMe, defined as time spent on different SoMe sites such as Facebook, YouTube, and Wikipedia, was associated with help-giving and moral courage among university students in Finland (mean age = 26 years). These studies did not fulfill the eligibility criteria and thus were not included in the review.…”
Section: Discussionmentioning
confidence: 99%
“…To date only a few studies have explored the effects of personality on OPB. For example, openness was found to be positively associated with moral courage and help-giving both in real life and online (Kinnunen et al, 2016); and agreeableness and conscientiousness were positively associated with online information-sharing (Deng et al, 2017). These indicated that extroverted and open-minded (e.g., imaginative, curious) individuals tend to behave more positively online.…”
Section: Personality and Opbmentioning
confidence: 99%
“…This citation suggests that introversion and neuroticism may also be negatively associated with OPB. But the effects of personality on OPB have not yet been soundly established, because previous studies have not used a comprehensive measure of OPB (Kinnunen et al, 2016;Deng et al, 2017), or have not directly investigated the roles of big five traits (Guo et al, 2018a).…”
Section: Personality and Opbmentioning
confidence: 99%
“…Issues, such as virtual reality in context of Industry 4.0 (Kovar, Mouralova, Ksica, Kroupa, Andrs & Hadas, 2016) [5], moral and ethical aspects of behaviour in virtual networks (Kinnunen, Lindeman, & Verkasalo, 2016) [6], dangers of social networking with an emphasis on gender aspects (Brooks & Longstreet, 2015) [7], effect analysis of Industry 4.0 to higher education (Baygin, Yetis, Karakose & Akin, 2016) [8], standardisation of communication of industrial networks in Industry 4.0 (Halenar, Juhasova & Juhas, 2016) [9], technoethics (Grebenshchikova, 2016) and humanitarian expert assessment of technosciences (Aseeva, 2016) [10,11], new values of the society (Kamensky, 2016) [12], the new di gital Industry 4.0 technological order in the context of the complexity paradigm (Roblek, Meško & Krapež, 2016) [13], are being researched by foreign scholars.…”
Section: Brief Literature Reviewmentioning
confidence: 99%